Performance Improvement on a Finance Company (A Case Study Inside Commercial Business Division of PT XYZ) - Ksatria Budi, Moch Wahyu; Zulbainarni, Nimmi; Ekananta, Arry (Journal Research of Social Science, Economics, and Management, 2026)
The financial industry is one of the many economic sectors that make a huge contribution to a country’s GDP (Gross Domestic Product). Financing companies are among its contributors; hence, they need top performance to secure their position as a national benefactor. This study revolves around performance management inside a division of one of Indonesia’s top financing companies, PT XYZ. Performance management itself relies on several indicators, including leadership, environment, motivation, engagement, and satisfaction. Thus, this study aims to explain which indicators affect employees’ performance the most. This study used data gathered from 90 people in the Commercial Business Division; data collection was done using Google Forms, and analysis was conducted through the SEM-PLS method. The results of this study confirm how each of the aforementioned indicators affects employees’ performance. Moreover, work motivation was the only indicator with the slightest impact on employees’ performance in PT XYZ’s Commercial Business Division. The implications of the findings suggest that performance improvement in this division can be optimized through an integrated approach that emphasizes enhancing leadership capacity and fostering a more collaborative work environment, rather than relying solely on short-term motivational incentives. These findings provide a basis for management to design more effective leadership development programs and work environment policies that support sustained work engagement and job satisfaction.